The effect of religiosity level on entrepreneurial sustainability of Muslim millennials: A case study of the Indonesian family life survey - Moh Najikhul Fajri; Siti Munawaroh (Review of Islamic Social Finance and Entrepreneurship, 2023)
Purpose – This study aims to examine the relationship and influence of the level of religiosity (obedience and piety) on stable business success for millennial Islam in Indonesia.Methodology – This study uses multinomial logit qualitative response regression to estimate religiosity's impact on business success. This study uses 5,252 individuals who are Muslim and have their businesses in IFLS data. Religiosity is measured through the level of the piety of millennial Muslims, while business success is proxied by using profitability.Findings – The results show that the religiosity of the millennial generation has a significant positive effect on the profitability of medium and low-class businesses. Meanwhile, the religiosity level of the millennial generation was also found to have a significant adverse effect on the profitability of upper-level businesses. On the other hand, a better level of millennial education and asset ownership also contributes to one's chances of getting a much higher profit than others. Finally, Muslims in urban areas get better profits than those in rural areas.Implications – Most millennial Muslims in the upper-class profitability have lower religiosity than other classes. It indicates that more and more people are involved in businesses that have the potential to violate religious values and are sure to be less obedient to worship. It is highly correlated with the amount of acquisition he gets. Meanwhile, for other classes, for example, the profit obtained is much lower, correlated with the habit of worshiping and religious observance, but does not rule out daily work and business so that sustainability is still obtained.Originality – No previous research has discussed the influence of the level of religiosity associated with business success among Muslim millennials.